Depression and personality: the impact of personality dysfunction on quality and severity of depressive symptoms and the moderating role of culture - Köhling, Johanna (2015)
Background: This dissertation project aims to help clarify to what extent – and under which circumstances – different forms of personality dysfunction affect the clinical presentation and severity of depression. Borderline Personality Disorder (BPD) is counted among the most severe forms of personality pathology (Hooley, Cole, & Gironde, 2012). Furthermore, there is literature describing distinct characteristics of depression experience in BPD patients (see Silk, 2010). Nevertheless, several issues with regard to “borderline-depression” remain unclear. In addition, Klein and colleagues (2009) suggested that future research should identify moderators of the personality-mood relationship. Hence, another focus of this project lies on the degree to which the relationship between personality and depression varies by cultural context. Methods: The first study provides a systematic review of depression quality, and a meta-analysis of depression severity in BPD patients compared to those with depressive disorders (DeDs). Based on a systematic literature search, 26 studies were identified for systematic review and 35 studies were included for meta-analysis. The review focused on different forms of depressive symptoms, affective impairment, self-evaluation, and negative interpersonal experiences. Besides overall group differences, the meta-analysis also examined different potential moderators of effect sizes. The second study employs ambulatory assessment methodology to explore affective instability and reactivity in 20 patients with major depressive disorder and BPD (MDD+BPD-group), and 21 patients with depression only (MDD-group). Participants reported on current affect, daily events, and attribution of affective states to events five times per day over a seven-day period. Study three compares the implications of personality dysfunction for depression severity in Chile and Germany. 30 Chilean and 30 German women matched for age and depression severity completed the Self-Construal Scale, Center for Epidemiological Studies Depression Scale, Depressive Experiences Questionnaire, and an inventory assessing overall personality functioning (OPD-Structure Questionnaire). Results: Findings of study one indicate that depression quality in BPD is characterized by higher anger/hostility and self-criticism. There was no difference in depression severity between BPD and DeD groups, and a high level of heterogeneity. Moderator analyses revealed lower depression severity in BPD patients without comorbid DeDs, but higher severity in BPD patients with comorbid DeDs compared to depressed controls. Results of study two do not indicate higher affective instability in the MDD+BPD-group. Depressed patients with BPD reported less subjectively perceived affective reactivity, while actual associations between events and affect were not different between groups, except for one finding: In MDD+BPD patients, overall mood was lower after being alone. In study three, culture moderated the relationship between dependency and depression, with higher dependency predicting higher depression in German but not in Chilean women. Self-criticism and impaired personality functioning were positively related to depression in both countries. Discussion: Results suggest high variability in depression severity across BPD patients, point toward the consideration of comorbid DeDs, and lend partial support to a BPD-specific depression quality. Furthermore, findings from ambulatory assessment question affective instability and suggest impaired attribution of mood changes and less tolerance of being alone as specific for depression in BPD. The intercultural comparison indicates that the adaptiveness of dependency seems to vary across cultures, while the implications of negative self-evaluation and broader concepts of personality dysfunction might be more universal. Main limitations of the current project lie in small sample sizes (studies two and three) and the cross-sectional research designs of studies one and three.